Aspiration for the bolshevik revolution in Germany and the Baltic peace barrier of 1923 - Butkus, Zenonas (History / Istorija, 2020)
The article investigates how and why new modern states, which emerged in the Baltic region after the First World War, became a barrier for the expansion of Bolshevik Russia into the depths of Europe. It has been established that the most striking attempt of exporting the Bolshevik Revolution took place in 1923, when an attempt to inspire the Communist coup in Germany was planned, with the intention to redeploy hundreds of thousands of Red Army troops, stationed at the western borders of the USSR, in the hope that the Baltic States and Poland would not hinder the army’s passage to Germany. However, the Balts and Poles, having withstood the Bolshevik pressure without succumbing to their threats and promises of rendering help, refused to let the Red Army get across their respective territories, even under the guise of a different cause. This venture of the Bolshevik had failed, due to the firm stance taken by four countries and due to the lack of a stronger revolutionary enthusiasm among Germans.